Perancangan Sistem Informasi Inventori untuk Pengecekan Expired Date pada Divisi Baby PT. Aeon Indonesia Cabang Jakarta Garden City - Santoso, Atikah Yuniar; Kostini, Nenden (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The inventory information system for checking expired dates is a computer-based system designed to manage expired dates, aiming to facilitate better control of product expiry within the sales. PT AEON Indonesia, a retail company with multiple divisions, includes the Baby division, specializing in various baby necessities and equipment. Among the many products sold in the Baby division, some have a shelf life, yet checking their expired dates is still done manually, inspecting one item after another. This manual process has proven to be time-consuming and demands considerable human resources, potentially disrupting other retail operations. The design of an inventory information system for checking expired dates was initiated due to the weaknesses of the manual system. The research objective is to create a prototype inventory information system that employs a coloring method within a specific time range, ensuring increased effectiveness and efficiency in managing expired dates.